Pengolahan Air Asam Tambang dengan Limbah Tempurung Sawit untuk Adsorpsi Fe, Mn, dan pH Pond - Evo Kristina; Agus Wirnarno; Harjuni Hasan; Windhu Nugroho; Lucia Litha Respati (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2025)
One of the negative impacts of the mining process is acid mine drainage which is formed from the oxidation of minerals containing iron sulfur, such as pyrite (FeS2) and pyrothite (FeS) by oxidizers such as water and oxygen. To handle or control acid mine drainage, one way is to use activated carbon or often referred to as activated charcoal, which is a type of carbon that has a very large surface area. Charcoal is a porous solid that contains 85% to 95% carbon, produced from materials containing carbon by heating at high temperatures without oxygen (pyrolysis). Activated carbon made from palm shells is an adsorbent that can be used to treat coal mine acid water, so that the water meets standards for flowing into the environment. This study used concentration variants of 4 grams, 6 grams, 8 grams and contact times of 30 minutes, 60 minutes and 150 minutes. The results of this study show that the concentration of palm oil shell activated carbon adsorbent influences the reduction of iron (Fe) and manganese (Mn) metal levels as well as the pH conditions in acid mine drainage water. The higher the concentration and the longer the contact time, the more heavy metals are adsorbed, the contact time is the highest. The optimal concentration in this study was 150 minutes and the optimal concentration was 8 grams with physical activation.